Age-related feeding behaviour and foraging efficiency in Kelp Gulls Larus dominicanus attending coastal trawlers in Argentina - Bertellotti, Néstor Marcelo (2000)
We studied age-related differences in feeding behaviour and foraging success of Kelp Gulls Larus dominicanus feeding on fishery discards at trawl vessels in northern Patagonia, Argentina. Kelp Gulls consumed fish by direct capture and intraspecific kleptoparasitism. Direct capture rate increased significantly with age. Juveniles dropped a higher proportion of handled fish than older birds. Intraspecific kleptoparasitism involved gulls of all age-classes and was recorded in all hauls. The percentage of successful attempts was similar among different age-classes. However, juveniles and immatures attempted to steal prey more frequently and therefore obtained more prey than expected. The proportion in which each feeding method (direct capture and kleptoparasitism) contributed to overall fish consumption varied significantly among age-classes. Juveniles obtained most of the food through kleptoparasitism (72%), while immature, subadult and adults consumed prey mostly through direct capture (77, 91 and 92%, respectively). Using both feeding methods, Kelp Gulls swallowed 87.6% of the discarded fish that they handled. However the percentage of fish swallowed over total handled fish were different among age-classes (juveniles: 45.5%; immatures: 70.8%; subadults: 83.3%; adults: 94.8%). Kleptoparasitism may be used as an alternative strategy to compensate the lower efficiency of young birds.